Adherence to Pre-pregnancy DASH Dietary Pattern and Diet Recommendations from the American Heart Association and the Risk of Preeclampsia (OR35-06-19) - Arvizu, Mariel (Curr Dev Nutr, 2019)
OBJECTIVES: Because the relationship between diet and hypertensive disorders of pregnancy (HDPs), including preeclampsia, remains unclear we aim to evaluate the association between pre-pregnancy adherence to the American Heart Association (AHA) diet recommendations and the Dietary Approaches to Stop Hypertension (DASH) dietary pattern with risk of developing preeclampsia (PE). METHODS: Our prospective cohort study included 20,024 pregnancies from 13,645 women enrolled in the Nurses’ Health Study II (NHS2) (1991 to 2007). Pre-pregnancy diet was measured in 1991 by a semi-quantitative food frequency questionnaire and updated every four years. Pregnancy outcomes were self-reported every 2 years during follow-up. We derived the DASH scores based on the intake of 8 food groups (fruits and fruit juices, vegetables, whole-grain, red and processed meats, nuts and legumes, sugar sweetened beverages, and sodium). The AHA score was derived from 5 food groups (fruits and vegetables, whole grain, fish, SSBs and sodium) consistent with AHA dietary guidelines to reduce hypertension in the general population. We estimated the RR and 95% CIs of PE by log-Poisson regression employing generalized estimating equations and adjusting for total energy intake, age at pregnancy, BMI, physical activity, parity, smoking status, infertility, marital status, multivitamin use, and gestational diabetes. RESULTS: HDPs were reported in 1,089 (5.4%) pregnancies, of which 505 (2.5%) were PE. The DASH score (max points = 40) ranged from 16 to 32 points and the AHA score (max score = 50) ranged from 18 to 41 points in our population. Compared to women in the lowest quintile of adherence to the AHA, the RR (95%CI) of PE in quintiles 2, 3, 4, and 5 were 0.88 (0.68, 1.14), 0.87 (0.66, 1.15), 0.83 (0.64, 1.09), and 0.79 (0.60, 1.06), respectively (p-trend = 0.09). Similarly, the RR (95%CI) of PE among women in increasing quintiles of adherence to the DASH score was 0.88 (0.68, 1.13), 0.72 (0.55, 0.94), 0.80 (0.61, 1.05), and 0.62 (0.45, 0.84) compared to women in the lowest quintile (p-trend = 0.002). CONCLUSIONS: Stronger pre-pregnancy adherence to the DASH dietary pattern was inversely associated to developing PE among participants of the NHS2. FUNDING SOURCES: Supported by National Institutes of Health grants UM1-CA176726, P30-DK046200, U54-CA155626, and T32-DK007703-16.